Effect of Simulated and Real Aircraft Cabin Environments on Tear Film Parameters in Dry Eye Disease: A Meta-Analysis - Jelly Vianti Fransisca Oeitano; I Gusti Ayu Made Juliari; Ida Ayu Ary Pramita; I Made Ady Wirawan (HM Publisher, 2026)
Background: Air travel exposes passengers to environmental stressors, such as reduced cabin pressure and low humidity, which may exacerbate ocular surface conditions, particularly pre-existing dry eye disease (DED). This meta-analysis quantifies the impact of real and simulated aircraft cabin environments on tear film parameters, ocular surface biomarkers, and intraocular pressure (IOP). Methods: Following PRISMA 2020 guidelines, a systematic search (January 2000–March 2026) identified ten eligible studies comprising 445 participants, with two providing complete quantitative data for meta-analytic pooling (10 effect sizes). Results: Using a random-effects model, the overall pooled standardised mean difference (SMD) was 0.97 (95% CI: -0.67 to 2.61), indicating a large but non-significant effect with substantial heterogeneity (I2 = 97.23%). Subgroup analyses revealed a non-significant pooled effect for tear film outcomes (Hedges' g = 0.71), contrasted by a significant elevation in IOP for gas-filled eyes (g = 1.92; p = 0.001). Despite the non-significant overall pooled estimate, individual effect sizes demonstrated large, clinically meaningful reductions in tear break-up time (TBUT) and significant increases in both corneal staining and inflammatory biomarkers (MMP-9 and IL-6). Egger's test showed no publication bias, though GRADE certainty remained low to very low. Conclusion: Aircraft cabin environments induce clinically significant deteriorations in tear film stability, ocular surface integrity, and inflammation, alongside significant IOP elevations in susceptible individuals. These findings underscore the necessity of pre-flight ocular counselling and targeted preventive strategies for at-risk passengers, highlighting the need for future large-scale, standardised investigations.